EXPERIENCE OF MANAGING SOMATIC RIGHTS OF A CHILD IN FOREIGN COUNTRIES - Navrotskyi, O. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2017)
the article is devoted to the coverage of the experience of administering the somatic rights of the child in foreign states at the present stage. Some aspects of the organizational and legal protection of children's biological rights in such states as France, Belgium, Andorra, India, the USA and some other states are considered. Attention is focused on the fact that in Ukraine only the legislation on the somatic rights of the child is being formed.